Overall, sex-and race/ethnicity-specific prevalence of thyroid dysfunction in US adolescents aged 12-18 years - Jianzhou Chen; Lingling Zhang; Xiaowen Zhang (Frontiers Media S.A., 2024)
BackgroundThyroid dysfunction significantly affects the health and development of adolescents. However, comprehensive studies on its prevalence and characteristics in US adolescents are lacking.MethodsWe investigated the prevalence of thyroid dysfunction in US adolescents aged 12-18 years using data from the National Health and Nutrition Examination Survey (NHANES) 2001-2002 and 2007-2012 cycles. Thyroid dysfunction was assessed using serum thyroid-stimulating hormone (TSH) and free thyroxine (fT4) measurements. We analyzed the prevalence across demographic subgroups and identified associated risk factors.ResultsThe study included 2,182 participants, representing an estimated 12.97 million adolescents. The group had a weighted mean age of 15.1 ± 0.06 years, with males constituting 51.4%. Subclinical hyperthyroidism emerged as the most prevalent thyroid dysfunction, affecting 4.4% of the population. From 2001-2002 to 2011-2012, subclinical hyperthyroidism remained consistent at 4.99% vs. 5.13% in the overall cohort. Subclinical and overt hypothyroidism was found in 0.41 and 1.03% of adolescents respectively, and overt hyperthyroidism was rare (0.04%). The prevalence of thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb) positivity in the overall population were 5.8 and 9.8%, respectively. Positivity for TgAb was risk factors for hypothyroidism, while older age, female and Black Americans were risk factors for hyperthyroidism. Female adolescents and adolescents with an older age were more likely to be positive for TPOAb and TgAb, while Black and Mexican Americans had a lower risk of TPOAb and TgAb positivity.ConclusionSubclinical hyperthyroidism was the most common form of thyroid dysfunction, and its prevalence remained stable from 2001-2002 to 2011-2012. Notable disparities in the prevalence of hyperthyroidism and antibody positivity were observed among different age, sex and racial/ethnic groups.